Systematic genetic assessment of hearing loss using whole-genome sequencing identifies pathogenic variants - Jung Ah Kim; Seung Hyun Jang; Sun Yung Joo; Se Jin Kim; Jae Young Choi; Jinsei Jung; Heon Yung Gee (Experimental and Molecular Medicine)
Abstract Hearing loss is a clinically and genetically heterogeneous sensorineural disease that affects approximately 1 out of 1000 newborns. For the molecular diagnosis of genetic hearing loss, target panel or whole-exome sequencing (WES) have been widely used due to their cost-effectiveness and efficacy. Despite the advantages of WES, the plausible diagnoses in a substantial number of patients remain elusive due to its limited coverage. Here we utilized whole-genome sequencing (WGS) on a large cohort of individuals with hearing loss to overcome the drawbacks of WES and find the advantages of WGS. We implemented a systematic workflow to identify coding region variants, cryptic splice variants, mitochondrial variants, copy number variants, cis-regulatory variants and transposable element insertions. WGS was conducted on 140 families with hearing loss. Causative variations were identified in 37 of these families, accounting for 26% of the total. WGS possessed the capability to find genetic variations that are not identifiable using WES. The identified variants by WGS in this study encompassed aberrant splicing variants in EYA1 and CDH23, mitochondrial variants in MT-RNR1 and MT-CO1, structural variants in STRC, and Alu insertion in SLC17A8. These findings highlight the benefits of WGS. With the decreasing cost of WGS, its usage will become more prevalent, allowing more precise identification of the genetic causes of hearing loss.